2007
DOI: 10.1007/s10792-007-9182-2
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring cataract surgical outcome in a Nigerian mission hospital

Abstract: The main cause of poor visual outcome in our centre is unsuspected co-morbidity. In spite of this, there is potential for good quality cataract surgery in Africa. As we pay more attention to appropriate patient selection we expect our outcome to improve. Provision of facilities for biometry would also be a great help in this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
5
9
1
Order By: Relevance
“…Intraoperative complications were acquired in 29 (1.4%) of eyes in our data, which is similar to some studies done in China [ 26 ], Africa [ 21 ] and India [ 5 ] and much less than other studies reported from Hong Kong [ 24 ], China [ 27 , 29 ] and Nigeria [ 23 ]. The difference is due to skill level of the surgeon operating, inclusion criteria etc.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intraoperative complications were acquired in 29 (1.4%) of eyes in our data, which is similar to some studies done in China [ 26 ], Africa [ 21 ] and India [ 5 ] and much less than other studies reported from Hong Kong [ 24 ], China [ 27 , 29 ] and Nigeria [ 23 ]. The difference is due to skill level of the surgeon operating, inclusion criteria etc.…”
Section: Discussionsupporting
confidence: 90%
“…Nearly 10% of the total patient did not return for 1–3 weeks follow-up and a third did not return for the 4–11 week follow up. This is similar to follow up rates seen in other developing countries [ 6 , 23 ]. It is likely that there were issues related to accessing services for those who did not return for follow-up and this needs to be further investigated.…”
Section: Discussionsupporting
confidence: 89%
“…A single publication from an eye hospital in Nigeria, however, reported poor postoperative vision outcomes [109]. Similarly, laparoscopic radical hysterectomy, other obstetric services, and repair of congenital anomalies can both be performed in LMIC specialized hospitals with outcomes similar to those found in the United States [105, 110113].…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of boxers with a cataract (34.8 years) was significantly higher ( P =0.004) than that of those without cataract (26.5 years). However, the mean age of boxers with cataracts is lower than that of patients with cataracts in the general population, which varies from 58 to 62 years, according to surveys carried out in Africa 16,17. This suggests that cataracts may appear earlier in boxers.…”
Section: Discussionmentioning
confidence: 99%